Right to Occupational Safety: Prevalence of Latent Tuberculosis Infection in Healthcare Workers. A 1-Year Retrospective Survey Carried out at Hospital of Lecce (Italy) - Gabriele d'Ettorre; Stela Karaj; Prisco Piscitelli; Osvaldo Maiorano; Carmen Attanasi; Roberta Tornese; Eugenia Carluccio; Paolo Giannuzzi; Enrico Greco; Giancarlo Ceccarelli; Gabriella d'Ettorre; Giambattista Lobreglio; et al. (MDPI AG, 2023)
Background: Prevention of latent tuberculosis infection (LTBI) in healthcare workers (HCWs) to ensure the "Right to Occupational Safety" is a special challenge globally, as HCWs have a higher risk of acquiring the infection in hospital settings because of frequent close exposure to patients suffering from tuberculosis (TB). Methods: Aretrospective study was performed with the aim of assessing the prevalence of LTBI related to demographical and occupational risk factors among HCWs employed in a large hospital in Italy. The study involved 1461 HCWs screened for LTBI by Mantoux tuberculin skin test (TST) and then confirmed with Interferon Gamma Release Assay (IGRA) test in case of positivity. Immunosuppressed and BGC-vaccinated workers were tested directly with IGRA. Results: LTBI was diagnosed in 4.1% of the HCWs and the prevalence resulted lower than other studies conducted in low TB incidence countries. The variables significantly linked with higher frequency of the infection were: age ≥40 years (OR = 3.14; 95% CI: 1.13-8.74; p < 0.05), length of service ≥15 years (OR = 4.11; 95% CI: 1.48-11.43; p < 0.05) and not being trained on TB prevention (OR = 3.46; 95% CI: 1.85-6.46; p < 0.05). Not trained HCWs presented a higher risk of LTBI also after adjustment for age and length of service, compared to trained HCWs. Conclusions: screening of HCWs for LTBI should be always considered in routinely occupational surveillance in order to early diagnose the infection and prevent its progression. Safety policies in hospital settings centered on workers' training on TB prevention is crucial to minimize LTBI occurrence in HCWs.